Assessing the creativity & innovation level of IT companies: The case of Denmark - René Victor Valqui Vidal; Lene Sørensen; U. Holmetoft; M. Gottfredsen (Colegio de Economistas de A Coru\~na, 2007)
Increasingly, the creativity and innovation potentials are becoming key factors for IT companies on an ever growing market, The Danish IT companies appear to have a strong base for competing with the rest of the world however it is clear that the companies have difficulties in managing their innovative potentials. This paper presents results of a research study made of 6 Danish IT companies with differing size. The study has focused on providing a first attempt in evaluating the companies' creative and innovative potentials. The paper illustrates how this problem has been approached using a combination of transparent and qualitative techniques. The paper cconcludes that the creative and innovative potentials can be qualitatively evaluated and that this can be the starting point for the development of a strategy concerning the development of creativity and innovation in a company.
Keywords: 330; IT-Industrie; Kreativität; Innovationsmanagement; Dänemark